86. Health Resource Burden of Influenza Among the Elderly with Underlying Conditions in the United States. (31st December 2020) - Near, Aimee; Tse, Jenny; Young-Xu, Yinong; Hong, David K; Reyes, Carolina M
Abstract: Background: Seasonal influenza poses a substantial clinical and economic burden, despite influenza vaccination efforts. This study evaluates healthcare resource utilization attributable to influenza in elderly populations at increased risk of influenza-related complications. Methods: Elderly (≥ 65 years of age) patients (pts) with ≥ 1 influenza diagnosis (Dx) during influenza seasons from October 1, 2014 – March 1, 2019 were identified in the IQVIA PharMetrics ® Plus claims database. The earliest influenza Dx was the index date and pts had evidence of pulmonary, cardiovascular, or renal disease before index. Pts had ≥ 12 months continuous enrollment (baseline before index) and ≥ 30 days follow-up after index. Medically-attended influenza cases were identified by primary influenza Dx codes or any influenza Dx with a record of an influenza test within ±14 days. Influenza pts were 1:1 propensity score matched to pts without influenza using baseline demographic and clinical characteristics and baseline healthcare costs. All-cause hospital and emergency department (ED) visits and total healthcare costs during follow-up (30-day and in the index influenza season) were compared in the matched cohorts. Results: Baseline characteristics were balanced after matching. Elderly influenza pts had 3 to 7 times higher 30-day hospitalization rates compared to pts without influenza, including pts with congestive heart failure (41% vs. 8%), chronic obstructive pulmonary disease (35% vs. 6%), coronary artery disease (23% vs. 4%), and stage 5/end stage renal disease (ESRD)/dialysis (44% vs. 13%; all p< .05; Figure). Hospital and ED visit rates in the influenza season were 2 to 3 times higher in pts with vs. without influenza; ED visit rates were 49% vs. 23%, 44% vs. 18%, 37% vs. 14%, and 60% vs. 28% for the above cohorts, respectively (all p< .05). Mean total healthcare costs per patient per season were $3, 299 to $12, 398 higher in pts with vs. without influenza (all p< .05, except myocardial infarction and stage 5/ESRD/dialysis pts). Figure. All-cause 30-day hospitalization rates in matched cohorts of elderly patients with baseline comorbidities with and without influenza Conclusion: Hospitalizations, ED visits, and total healthcare costs are elevated in the elderly after evidence of medically-attended influenza, but to varying degrees depending on baseline comorbidities. Continued efforts to reduce influenza burden in high-risk populations are needed. Disclosures: Aimee Near, MPH, Employee of IQVIA; IQVIA paid by VIR Bio to complete research project (Consultant) Jenny Tse, MS, Vir Biotechnology, Inc. (Other Financial or Material Support, I am employed by IQVIA which was paid by Vir Biotechnology, Inc. to complete this study.) David K. Hong, MD, Vir Biotechnology (Employee) Carolina M. Reyes, PhD, Vir Biotechnology (Employee, Shareholder)